2015
DOI: 10.1016/j.arr.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

ABCC9/SUR2 in the brain: Implications for hippocampal sclerosis of aging and a potential therapeutic target

Abstract: The ABCC9 gene and its polypeptide product, SUR2, are increasingly implicated in human neurologic disease, including prevalent diseases of the aged brain. SUR2 proteins are a component of the ATP-sensitive potassium (“KATP”) channel, a metabolic sensor for stress and/or hypoxia that has been shown to change in aging. The KATP channel also helps regulate the neurovascular unit. Most brain cell types express SUR2, including neurons, astrocytes, oligodendrocytes, microglia, vascular smooth muscle, pericytes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 236 publications
(270 reference statements)
4
67
0
3
Order By: Relevance
“…This discrepancy in DZ sensitivities was well explained later by the data of Liu et al, who showed different sensitivity of SUR1 and SUR2 isoforms to DZ and established EC 50 for DZ activation of Kir6.1/SUR1 comprising channel expressed in HEK293 cells to be of the order of 10 µM, which resembled the so-called "mK ATP channel" [4]. Much later studies found the expression of Kir6.1/SUR1 channel in liver mitochondria [35], which was consistent with high sensitivity of liver mK ATP channel to DZ observed experimentally [7]. Meanwhile, in ventricle myocyte mitochondria predominant expression of "DZinsensitive" Kir6.2/SUR2A was established [32,40], although heart and liver mitochondria were shown to not much differ in their sensitivities to DZ [7].…”
Section: Mkatp Channels As the Target Of Diazoxidementioning
confidence: 75%
See 2 more Smart Citations
“…This discrepancy in DZ sensitivities was well explained later by the data of Liu et al, who showed different sensitivity of SUR1 and SUR2 isoforms to DZ and established EC 50 for DZ activation of Kir6.1/SUR1 comprising channel expressed in HEK293 cells to be of the order of 10 µM, which resembled the so-called "mK ATP channel" [4]. Much later studies found the expression of Kir6.1/SUR1 channel in liver mitochondria [35], which was consistent with high sensitivity of liver mK ATP channel to DZ observed experimentally [7]. Meanwhile, in ventricle myocyte mitochondria predominant expression of "DZinsensitive" Kir6.2/SUR2A was established [32,40], although heart and liver mitochondria were shown to not much differ in their sensitivities to DZ [7].…”
Section: Mkatp Channels As the Target Of Diazoxidementioning
confidence: 75%
“…So, SUR1 comprising channels were shown to be expressed in cardiac tissues [32,33], pancreatic beta cells (Kir6.2/SUR1 [4,10]), liver and liver mitochondria (Kir6.1/SUR1 [34]). SUR2A showed relatively high expression in cardiac and skeletal muscle cells [24,[32][33][34], whereas SUR2B was more broadly expressed in smooth muscle cells and brain [35,36]. In cardiac tissues SUR and Kir subunit distribution showed cell-specificity.…”
Section: K Atp Channels As Cellular Targets Of Diazoxidementioning
confidence: 96%
See 1 more Smart Citation
“…O KATP representa um sensor metabólito ao estresse e à hipóxia, auxilia na regulação da unidade neurovascular (NELSON et al, 2015). Logo, o gene ABCC9 e o seu componente polipeptídico, SUR2, ocupam uma posição intrigante para a vasorregulação no cérebro.…”
Section: Desenvolvimentounclassified
“…Contudo, valiosos estudos experimentais apontam algumas funções para esses canais como atividades relacionadas ao desenvolvimento e ao metabolismo celular. Isso corrobora para a relação entre o canal KATP e o gene ABCC9 no distúrbio da insônia (NELSON et al, 2015).…”
Section: Desenvolvimentounclassified